Investigation of the microstructure evolution in TP347HFG austenitic steel at 700°C and its characterization method - Zhang Yuetao (De Gruyter, 2021)
This article reports the microstructure evolution in TP347HFG austenitic steel during the aging process. The experiments were carried out at 700°C with different aging time from 500 to 3,650 h. The metallographic results show that the coherent twin and incoherent twin are existed in the original TP347HFG grains, while they gradually vanished with the increase of the aging time. After aging for 500 h, a lot of fine, dispersed particles precipitated from the matrix, but they disappeared after aging for 1,500 h. When the aging time extend to 3,650 h, the precipitates appeared apparently coarse in TP347HFG steel, which include the M23C6 and σ phase; besides, the micro-hardness of TP347HFG also changes during the aging, which was closely related to the effect of dispersion strengthening and solution strengthening. The results of the nonlinear ultrasonic measurement reveal that the β′ of TP347HFG steel was also changed with the aging time. It first increased at 0–500 h, then reduced later, and increased finally at 1,500–3,650 h. The variation of β′ in TP347HFG was influenced by a combined effect of the twin microstructure and the precipitate phase, which indicate that the nonlinear ultrasonic technique can be utilized to characterize the microstructure evolution in TP347HFG.